Design and application of inter-hospital transfer form based on SBAR communication mode for transferring critically ill patients in the Psychiatric Department (基于SBAR沟通模式的院内转科交接单在精神科危重患者院内转科中的应用) - GU Liqin (顾丽琴); KONG Fanzhen (孔凡贞); JI Caifang (季彩芳); ZHU Xiaolan (朱晓岚) (中西医结合护理)
Objective To explore the application of inter-hospital transfer form based on SBAR communication mode for transferring critically ill patients in the Psychiatric Department. Methods A total of 188 critically ill psychiatric patients were selected as the research subjects, and were divided into control group (n=94) and observation group (n=94) according to the order of admission. The control group used the conventional inter-hospital transfer form for nursing handover, while the observation group used the self-designed standardized transfer sheet based on SBAR communication mode to assist the transfer. The incidence of adverse events in hospital transfer, the evaluation of nurses on hospital transfer and the satisfaction of patients' families on nursing work were compared between the two groups. Results The incidence of adverse events in hospital transfer in the observation group was lower than that in the observation group (3. 19% vs. 12. 77%, P＜0. 05). Except for issue of “access to important information” and “chance of problems consulting”, the dimensional score of Handover Evaluation Scale (HES) in the observation group was higher than that in the control group (P＜0. 05). The nursing satisfaction rate was 94. 57% in the observation group, indicating a high level of satisfaction among family members. Conclusion The inter-hospital transfer form based on SBAR communication mode can reduce the occurrence of transfer problems , help nurses improve the quality of transfer and handover, improve the patient's family satisfaction with nursing work, and ensure the safety of patients. It is worthy of promotion and application. (目的 探讨基于SBAR沟通模式的院内转科交接单在精神科危重症患者院内转运中的应用效果。方法 选选取2020年9月—11月住院的94例精神科危重患者为对照组, 采用常规的院内转科交接单进行交接; 另选取2020年12月—2021年2月住院的94例精神科危重患者为观察组, 采用根据SBAR沟通结构框架制作的院内交接单辅助交接。比较2组院内转科交接问题的发生率、护士对院内转科交接的评价情况及患者家属对护理工作的满意度。结果 观察组转运交接问题发生率3. 19%(3/94), 低于对照组的12. 77%(12/94), 差异有统计学意义(P＜0. 05)。观察组护理交接班评价量表(HES)各条目评分均高于对照组, 除“重要信息我总是可以收到”“我有机会请教我不理解的问题”条目外, 差异有统计学意义(P＜0. 05)。观察组满意度94. 57%, 提示满意度较高。结论 应用基于SBAR沟通模式院内转科交接单能够减少院内转科交接问题的发生, 提高转运质量, 提升患者家属对护理工作的满意度, 保证了患者的安全, 值得推广和应用。)